“OPEN ABDOMEN” TACTICS FOR DISSEMINATED PERITONITIS: INDICATIONS, COMPLICATIONS, AND TREATMENT RESULTS - Mustafakulov Ishnazar Boynazarovich, Tokhirov Sheroz Mardonkulovich, Djuraeva Zilola Aramovna; Mustafakulov Ishnazar Boynazarovich, Tokhirov Sheroz Mardonkulovich, Djuraeva Zilola Aramovna (Research Focus International Scientific Journal, 2026)
The open abdomen approach is used for the most severe forms of disseminated peritonitis, accompanied by abdominal sepsis and intra-abdominal hypertension syndrome. The aim of this study was to evaluate the indications, complication rates, and clinical efficacy of the open abdomen approach in patients with disseminated peritonitis. It was found that this approach is justified when the indications are strictly followed; however, it is associated with a high complication rate and requires an individualized approach and dynamic patient monitoring.